DEVELOPING “BLOOKET” AS A MEDIUM TO ENRICH STUDENTS’ VOCABULARY FOR THE SEVENTH GRADERS - Laili Masruroh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Vocabulary plays a crucial role in English language acquisition. Presently, the predominant challenge in Indonesia is that a significant number of students struggle to communicate proficiently in English due to their insufficient command of vocabulary. Consequently, devising effective strategies to impart vocabulary is crucial. One viable approach to address this challenge involves the utilization of media. Blooket, a computer-based medium, has been transformed into a potent educational tool employing the Research and Development (R&D) framework. R&D, as a research design, is instrumental in the creation and evaluation of new products through iterative experimentation. The research design encompasses key stages, including the validation of materials and media, as well as field assessments. Field evaluations were undertaken at a chosen Junior High School in Sidoarjo, with seventh-grade students participating in the study. The topic selected for enriching students' vocabulary was descriptive text. The primary aim was to ascertain the viability of implementing the developed media and gauge the perceptions of both educators and students during its application. Based on the outcomes derived from the implemented stages, it is evident that Blooket is well-suited for English language instruction. Not only does the game serve as a motivational tool for students, but it also mitigates the risk of student boredom during vocabulary learning sessions.